Pengembangan Model Pembelajaran Kebugaran Jasmani Komponen Kekuatan dan Kelenturan Berbasis Permainan “PKK” Siswa Kelas VIII SMPN 1 Malang - Danendra, Afid; Mu’arifin; Sanusi, Anwar (Universitas Negeri Medan, 2024)
Education plays a crucial role in optimally developing individual potential. In addition to enhancing academic abilities, education also aims to shape character and life skills, as emphasized by scholars such as Biesta (2015) and Zahro (2023). Physical Education (PE) contributes significantly to the achievement of holistic educational goals, not only in terms of physical development but also in instilling character values such as discipline, teamwork, and resilience. PE also has a positive impact on students’ cognitive function and mental health, supporting the overall learning process. The game-based learning model (PKK) is an innovative approach that can increase students’ interest and motivation in physical fitness education. This study employs the Research and Development (R&D) method using the ADDIE model to develop a learning model called